A Organização em rede e a comercialização de cooperativas/associações de catadoras e catadores de materiais recicláveis: a rede CATARECICLA - Sodré, Hercules Alves [UNESP] (2016)
The way (the) waste pickers (s) of recyclable materials has been organized today, makes this working class get an improvement in production and income for those people who are on the margins of social vulnerability by networking joining forces between (the) same (the). It's up to that study, analyze about this social phenomenon, the process of consolidation and improvement of their lives, taking as spatial area to CATARECICLA network